5PSQ-106 Implementation of advanced therapy medicinal products (ATMP) reconstitution in a university teaching hospital in France: proposal of a decision-making algorithm. (23rd March 2022) - Benjamin, F; du Repaire, T; Montana, M; Fanciullino, R; Ausias, N; Deluca, B; Gauthier Villano, L; Pourroy, B
Abstract : Background and importance: ATMP (genetically modified organisms (GMO) ones or not) use is rising in oncology, and requires the establishment of a specific organisation to ensure a safety circuit. Aim and objectives: To implement ATMP reconstitution in our institution we built a decisional algorithm for risk and feasibility assessment for each ATMP. Material and methods: A team of seven oncology pharmacists was constituted to take into account the complexity of the organisations in our institution and associate several pharmaceutical competencies. They first identified a flow diagram based on critical steps. For each step, according to regulations, professional guidelines and expertise field of each pharmacist, three brainstorming sessions were organised to identify main subprocesses and key points which must be evaluated for each ATMPs. Critical points were retained and a decision-making algorithm for ATMP risks and feasibility assessment, based on a yes/no dichotomy progression, was built and validated with circuit of ATMP in clinical trials (CT) ever conducted in our institution. Results: The decision-making algorithm we built consists of six steps (ATMP nature, storage conditions, thawing conditions, preparation of a not-GMO ATMP, preparation of a GMO-ATMP, waste disposal). Each step consisted of several questions (34). If a step fails, ATMP can not be used. Critical points such as security storage back-up or qualification of waste inactivation process are yet to be implemented into the algorithm. Moreover, as some facilities might routinely be unavailable yet in hospital pharmacies (storage in vapor phase nitrogen), the algorithm takes into account availability of these facilities outside of the pharmacy through subcontracting with a warranty of ATMP quality. After retrospective scrutiny of our algorithm with ATMP circuits ever conducted in CTs (talimogene laherparepvec, axicabtagene ciloleucel), it appeared to meet all our needs. Conclusion and relevance: This tool was used prospectively to implement tisagenlecleucel, onasemnogene abeparvovec and soon betibeglogene autotemcel in our centre. Furthermore, the French Regional Health Agency identified it as a key point to make our ATMP circuit secure. References and/or acknowledgements: Conflict of interest: No conflict of interest